2013
DOI: 10.1519/jsc.0b013e31827f06ae
|View full text |Cite
|
Sign up to set email alerts
|

The HIF1A Gene Pro582Ser Polymorphism in Russian Strength Athletes

Abstract: Hypoxia-inducible factor-1α (encoded by HIF1A gene) controls a number of genes that are implicated in various cellular functions including glycolysis and cell proliferation and differentiation. The rs11549465 C > T polymorphism in the HIF1A gene, which produces the amino acid substitution Pro582Ser, increases protein stability and transcriptional activity and, therefore, improves glucose metabolism. The aim of our study was to investigate the association between the HIF1A Pro582Ser polymorphism and elite stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 22 publications
0
18
0
3
Order By: Relevance
“…highly elite (25.0%)). These results were replicated in three cohorts of 158 Polish power-orientated athletes [218], 208 Russian power-oriented athletes (122 weightlifters and 86 wrestlers) [219], and 110 Ukrainian power-oriented athletes [220], but not in 81 Israeli sprinters [221]. Furthermore, the 582Ser allele was significantly associated with an increased proportion of fast-twitch muscle fibers in m. vastus lateralis of all-round speed skaters [217].…”
Section: Hif1a 582ser Allelementioning
confidence: 75%
“…highly elite (25.0%)). These results were replicated in three cohorts of 158 Polish power-orientated athletes [218], 208 Russian power-oriented athletes (122 weightlifters and 86 wrestlers) [219], and 110 Ukrainian power-oriented athletes [220], but not in 81 Israeli sprinters [221]. Furthermore, the 582Ser allele was significantly associated with an increased proportion of fast-twitch muscle fibers in m. vastus lateralis of all-round speed skaters [217].…”
Section: Hif1a 582ser Allelementioning
confidence: 75%
“…Subsequent research has confirmed the association between the R allele and power performance, although the link between the X allele and endurance is less clear [49]. Other replicated SNPs found to affect athletic performance include ACE I/D [50 -52], PPARGC1A Gly482Ser [53 -55], GABPB1 (rs7181866) [56,57], BDKRB2 +9/-9 [58,59], and HIF1A Pro582Ser [60,61].…”
Section: Gene Polymorphisms and Exercise Adaptationmentioning
confidence: 99%
“…HIF-1α geni esas olarak oksijen tüketimi ile ilişkilendirilmesine rağmen, oksijenden bağımsız mekanizmalarla da düzenlenmektedir. Örneğin, HIF-1α'nın insülin benzeri büyüme faktörü (IGF) -1'ü aktive ettiği bilinmektedir [99]. Cıeszczyk…”
Section: Hypoxia İnducible Factor 1α (Hif1a)unclassified